Behavior of Demountable Connections with Taper Threaded Mechanical Coupler (TTC) and Rebar Anchor Under Tension Load - Ivan Milićević; Branko Milosavljević; Milan Spremić (Buildings)
Composite and mixed steel-concrete buildings, apart from high structural efficiency, have great potential in terms of reuse of structural elements at the end of the life of the buildings. The use of most demountable connectors can assure the reuse of steel elements; however, the reuse of reinforced concrete (RC) elements and embedded connectors remains relatively uncertain due to potential damage of connectors during disassembly. One of the possible solutions to assure the reuse of all components could be to use demountable connectors assembled from a demountable bolt and an embedded mechanical coupler with a rebar anchor. The key challenge for practical implementation of this type of demountable connector is adequate analysis under tension loads, due to a lack of design recommendations. This paper presents experimental investigations of the connection with demountable connectors with mechanical couplers and rebar anchors, located close to the concrete edge, under pure tension load. Nine pull-out tests on single connectors embedded in the RC element and six in-air tests on bare connectors were conducted in order to define the global behavior of the connection and the local behavior of the connector, respectively. The influence of concrete strength (concrete class C20/25 and C30/37), connector diameter (with M16 and M20 bolts), and bolt grade (grades 5.8 and 8.8) on the connection behavior was discussed in terms of resistance, stiffness, deformation capacity, and failure modes. Ultimate resistance varied from 77 kN to 135 kN, with failure modes shifting from taper thread stripping to bolt fracture based on bolt grade. Based on the obtained test results, analytical equations for the calculation of tension resistance and overall deformation capacity of the connection were proposed.